111 In Vivo Performance of a Microfabricated Catheter for Intraparenchymal Delivery. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Brady, Martin; Singh, Deep; Anand, P.J.; Fleisher, Adam; Broaddus, William C.; Mata, Jaime; Olbricht, William; Raghavan, Raghu
Abstract: INTRODUCTION: Convection-enhanced delivery (CED) is an effective technique to bypass the blood-brain barrier (BBB) and deliver drugs directly into the brain parenchyma. However, several technical limitations must be addressed to increase its efficiency, repeatability, and effectiveness in clinical practice. METHODS: This study reports infusions of tracers of various sizes into the brain of a large mammal (pig) using a novel microfabricated catheter. Standard stereotactic procedures were used using the Medtronic Navigus Trajectory Guide kit to target the anatomy. Infusions through the microcatheter at various infusion rates were evaluated for possible backflow or reflux up the outside of the catheter, which has proved to be a problem in CED infusions, especially at high infusion rates. Real-time magnetic resonance (MR) imaging was used to examine the distributions of the tracers and their concentration profiles in the parenchyma. In-line catheter pressures were monitored for all infusions. Infusions were carried out in porcine white matter, thalamus, and putamen. RESULTS: The extent of backflow, if any, and concentration profiles were determined for several MR contrast reagents and fluorescent dyes with sizes that are typical of small molecules, therapeutic proteins and an adeno-associated virus (AAV). Infusion flowrates up to 40 μL/min were achieved without evidence of backflow of infusate along the catheter. The ratio of the volume of distribution in tissue to the infusion volume (Vd/Vi) was similar for all infused reagents. The in-line pressures were consistent with theoretical values for flow through a micro-lumen. CONCLUSION: The microfabricated catheter was able to target different cytoarchitectures with precision using standard functional stereotactic techniques and deliver small and large molecules at high infusion rates without evidence of backflow. The measured distribution volumes indicated that all infusates were readily convected through the interstitial space regardless of molecular size.